2021
DOI: 10.1080/00220388.2021.1873286
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Sub-national Government and Regional Development in Africa

Abstract: Despite widespread interest in government quality and economic development, the role of sub-national government has been largely overlooked. This represents an omission in Africa, given ongoing processes of devolution in much of the continent. In this article, we consider the impact of sub-national government institutions on economic development in 356 regions across 22 African countries. We create a novel index of sub-national government quality based on large-scale survey data and assess its impact on region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 75 publications
1
25
0
Order By: Relevance
“…In addition to the research on government quality and the returns of European Cohesion policy by Rodríguez‐Pose and Garcilazo (2015), several contributions have shown that local institutional quality impinges on economic growth through its effect on different policies and investments, such as interventions to promote entrepreneurship (Nistotskaya et al ., 2015; Aparicio et al ., 2016; Huggins and Thompson, 2016), regional competitiveness (Annoni and Dijkstra, 2017), innovation (Rodríguez‐Pose and Di Cataldo, 2015), productivity (Kaasa, 2016), industrial diversification (Cortinovis et al ., 2017), resilience (Ezcurra and Rios, 2019), or infrastructure (Crescenzi et al ., 2016). Similar work has been carried out outside Europe (for example, Rodríguez‐Pose and Zhang, 2019; Iddawela et al ., 2021). Overall, the bulk of this literature highlights that local government quality is a fundamental shaper of economic growth (Ketterer and Rodríguez‐Pose, 2018) and that the connection between the quality of local institutions and economic performance is achieved both directly and indirectly, through how variations in government quality shape the design, implementation, and monitoring of public policies.…”
Section: Quality Of Government and Economic Growthmentioning
confidence: 99%
“…In addition to the research on government quality and the returns of European Cohesion policy by Rodríguez‐Pose and Garcilazo (2015), several contributions have shown that local institutional quality impinges on economic growth through its effect on different policies and investments, such as interventions to promote entrepreneurship (Nistotskaya et al ., 2015; Aparicio et al ., 2016; Huggins and Thompson, 2016), regional competitiveness (Annoni and Dijkstra, 2017), innovation (Rodríguez‐Pose and Di Cataldo, 2015), productivity (Kaasa, 2016), industrial diversification (Cortinovis et al ., 2017), resilience (Ezcurra and Rios, 2019), or infrastructure (Crescenzi et al ., 2016). Similar work has been carried out outside Europe (for example, Rodríguez‐Pose and Zhang, 2019; Iddawela et al ., 2021). Overall, the bulk of this literature highlights that local government quality is a fundamental shaper of economic growth (Ketterer and Rodríguez‐Pose, 2018) and that the connection between the quality of local institutions and economic performance is achieved both directly and indirectly, through how variations in government quality shape the design, implementation, and monitoring of public policies.…”
Section: Quality Of Government and Economic Growthmentioning
confidence: 99%
“…In columns 1-3 of Table 7, I find that the correlation of the amount of research at the subnational level with population and GDP per capita is positive and highly statistically significant, while the correlation with international aid is positive but not statistically significant, closely paralleling the country-level results in columns 1-3 of Table 4. 27 Since the Global Peace Index and the Liberal Democracy Index are not available at the subnational level, I include different proxies for peacefulness and institutions -the number of ACLED conflict events and an index of subnational government quality derived from Afrobarometer survey data (Iddawela, Lee and Rodr íguez-Pose, 2021). Results in column 4 suggest that -conditional on the amount of research on the country as a whole, which is less in less peaceful countries with worse institutions -more research is done in subnational regions with more conflict events.…”
Section: Evidence From Subnational Datamentioning
confidence: 99%
“…The literature on the concept, measurement, causes, and correlates of sub-national institutional governance is not new-see Chachu et al (2020) for a recent review of this literature. From the seminal work of Putnam et al (1993) to recent attempts by Iddawela et al (2021), several authors have explored untapped spaces that contribute to our understanding of the relationship between sub-national governance and development. Putnam et al (1993) explore about 20 regional governments in Italy in their attempt to explain the striking sub-national variations in the country's development.…”
Section: Introductionmentioning
confidence: 99%
“…Putnam et al (1993) explore about 20 regional governments in Italy in their attempt to explain the striking sub-national variations in the country's development. More recently, Iddawela et al (2021) combine satellites data with the construction of sub-national government quality indices across 356 sub-national governments in 22 African countries to explain variations in regional development in Africa. The latter attempt, perhaps among few others, adds to the dotted landscape of studies that focus on developing regions, such as Africa.…”
Section: Introductionmentioning
confidence: 99%